Designing security policies for complex SCADA systems management and protection. (2016) - Feltus, Christophe; Khadraoui, Djamel
Supervisory control and data acquisition systems (SCADA) are required to deal with increasingly sensitive and crucial situations. The management and protection of these systems must constantly evolve towards integrated decisions support and policies driven by cyber security requirements. The current research stream in this area aims to foster the smartness of the field equipments and the management processes. SCADA components are governed by policies which depend on the components function as well as on the evolution of the crisis which also confer to the latter the latitude to react based on their own perception of the situation evolution. Existing work related to crisis management tends to consider that components evolve and are organised in systems but as far as we know, no systemic solution exists which integrates all of the above requirements. This paper proposes an ArchiMate® extension for SCADA with a broaden explanation of the behaviour endorsed in cyber-policy.